DEVELOPMENT OF POP-UP BOOK MEDIA BASED ON PROBLEM-SOLVING ON FRACTION MATERIAL - Jasmaniah Jasmaniah; Nurhayati Nurhayati; Fatma Zuhra (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to produce pop-up book media based on problem-solving in fractions in 4th grade of Elementary School that meet valid criteria and deserve to be developed. This research uses a development method that makes certain products and tests the effectiveness of these products. The development model used is the ADDIE model. Sampling used a random sampling technique with instruments in the form of media feasibility validation questionnaires given to 5 validators consisting of 3 expert validators and 2 Mathematics teachers. Based on the research and development results, problem-solving-based pop-up book learning media on fractional material developed through the ADDIE development model obtained an average feasibility percentage of 93.90%. At the same time, problem-solving-based pop-up book media that has been applied to students shows that 88.72% of students are happy with the learning.